A distribuição equitativa de riscos e danos como uma justificativa não agregativa da responsabilidade civil - Ana Luiza Braga Guatimosim (2020)
The research, through Barbara Fried's critique to non-consequentialists, seeks to ascertain whether Keating's theory of fair distribution of risk and harm can answer questions that other moral theories of tort law fail to answer. It is examined whether Keating's contractualism may suggest a non-consequentialist, non-aggregative way to the question proposed by Fried regarding the risks citizens have the right to impose on others. Once the barrier presented by Fried was overcome, the work is dedicated to analyzing the influence of the idea of fairness in tort law, as highlighted by Keating, and how this concept is decisive in the choice between tort law schemes present in political culture.